Implementation of the new public procurement Act no. 15, 2015: a case study of the local authorities (municipalities) in Namibia - Ochurub , Michael; Jeremiah, Andrew; Ochurus, Erna (Namibian Journal for Research, Science and Technology, 2022)
This paper articulates the implementation of new Public Procurement Act (No.15, 2015) in the Local Authorities (municipalities) in Namibia. This paper explores the concept of implementation with specific focus on how the decisions and plans based on the new procurement process were executed in practice within the Local Authorities in Namibia. Quantitative questionnaires were used and the numerical data obtained was analysed and presented in the form of numbers and statistics. The major findings of this paper show that the implementation process was not successful as the municipalities and its employees were not ready for the implementation of the new Public Procurement Act (No.15, 2015). The need for proper planning prior implementation was emphasized. It was found that key factors such as leadership and management aspects, communication, training of employees should be considered before implementation. This research adds great value as it addresses the need for a proper communication of the new system and leadership development to drive and manage the implementation process. The research also contributes to the body of existing knowledge as it alludes to people, as the most intangible components of readiness and when they are not ready, the results of implementation would be negative. Recommendations were made as outcomes of conclusions drawn from the data gathered during the research and are considered to have potential for improved and successful implementation of the new Public Procurement Act within the municipalities in Namibia.